A comparative clinico-radiographic analysis of regenerative endodontic procedure on immature necrotic permanent teeth using blood clot and PRF as scaffold: A retrospective study - Shruti Thakkar; Saraswathi Naik; Basappa Nadig; Shivani Bellal; Akshaya Thaliyil (Elsevier, 2023)
Objectives: To evaluate the clinical and radiographic success rate of blood clot and platelet rich fibrin (PRF) as a scaffold system in regenerative endodontic procedure in immature traumatized necrotic teeth.. Materials and methods: This retrospective study examined the records of 28 subjects with necrotic immature open apex due to trauma treated with blood clot or PRF as a scaffold in regenerative endodontic procedure. The disinfection was carried out with calcium hydroxide as an intra-canal medicament. The clinical outcome was recorded using a binary variable of presence or absence of pain and intra-oral swelling. The radiographic outcome was recorded for periapical healing using Ørstavik's Periapical Index and apical response using Chen and Chen index. Comparison of frequencies of categories of variables with groups was done using the chi-square test. The pairwise comparison of time intervals was done using Wilcoxon Signed Ranks Test. Results: Intra-group comparison of pain and intra-oral swelling had highly significant (p = 0.000) results for both groups over a period of 12 months. Inter-group comparison for clinical outcomes was insignificant. For the radiographic outcome, there was a statistically non-significant difference for periapical healing and apical response for both intra-group and inter-group comparisons. Conclusion: Both PRF and blood clot have a favourable outcome for a regenerative endodontic procedure with a disinfectant protocol using calcium hydroxide as intracanal medicament. Considering the cumbersome procedure involved in procuring PRF scaffold, especially in children, inducing bleeding can be considered a recommended method for a regenerative endodontic procedure.